ACTR-17. EVOPHOSPHAMIDE (TH-302) FOR RECURRENT GBM FOLLOWING BEVACIZUMAB FAILURE, FINAL RESULTS OF A MULTICENTER PHASE II STUDY. (5th November 2018) - Brenner, Andrew J; Reardon, David; Wen, Patrick; Huang, Shiliang; Fox, Peter; Muzi, Mark; Lee, Eudocia
Abstract: INTRODUCTION: Evophosphamide is a hypoxia-activated prodrug that, when activated in hypoxic conditions, (<0.5% O2), releases the bis-alkylating agent bromo-isophosphoramide mustard (Br-IPM). Our prior phase 1 study in recurrent GBM (rGBM) with dose expansion showed preliminary activity with a 24% objective response rate and a 26% PFS rate at 4 months. METHODS: A multicenter, single-arm, two-stage prospective study, non-blinded with combination therapy with bevacizumab at 10 mg/kg intravenously (IV) every 2 weeks and TH-302 at 670 mg/m2 IV every 2 weeks, in 6 week cycles, until disease progression. The primary endpoint was progression free survival at 4 months (PFS4). Patients underwent baseline assessment for hypoxic burden by 18F-misonidazole PET, dynamic susceptibility contrast (DSC) perfusion imaging, and serum sampling for biomarker analysis. RESULTS: 36 patients received study drug. Treatment was well tolerated, with adverse events as expected and the most common toxicity rash along the perineum. The PFS4 rate was 25% which met the primary endpoint and compares favorably with historical controls (10%). Biomarker analysis revealed progression to be correlated with Tmax on DSC perfusion (HR=0.8, 95% CI 0.66 to 9.96, p=0.02), ratio of enhancement on anatomic MRI Ratio (HR=9.37, 95% CI 1.18 to 74.5, p=0.03) and survival was most closely correlated with hypoxic volume on FMISO PET (HR=1.02, 95% CI 1 to 1.04, p=0.01). CONCLUSION: Evofosfamide has modest activity in bevacizumab refractory glioblastoma, with progression and survival correlated with radiographic features at baseline.